2018
DOI: 10.3389/fphys.2018.01164
|View full text |Cite
|
Sign up to set email alerts
|

Elevated pCO2 Affects Feeding Behavior and Acute Physiological Response of the Brown Crab Cancer pagurus

Abstract: Anthropogenic climate change exposes marine organisms to CO2 induced ocean acidification (OA). Marine animals may make physiological and behavioral adaptations to cope with OA. Elevated pCO2 may affect metabolism, feeding, and energy partition of marine crabs, and thereby affect their predator-prey dynamics with mussels. Therefore, we examined the effects of simulated future elevated pCO2 on feeding behavior and energy metabolism of the brown crab Cancer pagurus. Following 54 days of pre-acclimation to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 94 publications
3
16
0
Order By: Relevance
“…Our results showed that OA has a mixed effect on swimming crabs, with increased survival and retarded growth. The negative effect on growth is in line with findings published for other crab species such as larvae of H. araneus ( Walther et al, 2010 ; Schiffer et al, 2013 , 2014 ; Wang et al, 2018 ), Paralithodes camtschaticus , and Chionoecetes bairdi ( Long et al, 2013a , b ), as well as embryos of Petrolisthes cinctipes ( Carter et al, 2013 ; Ceballos-Osuna et al, 2013 ). Such a consensus between studies performed on different species, at different stages of development and with p CO 2 ranging from 710 to 3100 μatm, strongly supports crab sensitivity to OA.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results showed that OA has a mixed effect on swimming crabs, with increased survival and retarded growth. The negative effect on growth is in line with findings published for other crab species such as larvae of H. araneus ( Walther et al, 2010 ; Schiffer et al, 2013 , 2014 ; Wang et al, 2018 ), Paralithodes camtschaticus , and Chionoecetes bairdi ( Long et al, 2013a , b ), as well as embryos of Petrolisthes cinctipes ( Carter et al, 2013 ; Ceballos-Osuna et al, 2013 ). Such a consensus between studies performed on different species, at different stages of development and with p CO 2 ranging from 710 to 3100 μatm, strongly supports crab sensitivity to OA.…”
Section: Discussionsupporting
confidence: 89%
“…Ocean acidification has comprehensive effects on the growth and development ( Long et al, 2013a ), physiology and metabolism ( Maus et al, 2018 ), morphology ( Ren et al, 2017 ), and behavior of a variety of marine crabs ( Wang et al, 2018 ). However, the effects of OA have been reported only on the carapace morphology and behavior of juvenile P. trituberculatus ( Ren et al, 2017 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocean acidification can negatively affect benthic marine invertebrates, either directly, by altering physiological processes (Pan et al, ; Wang, Hu, Wu, Storch, & Poertner, ; Widdicombe & Spicer, ), or indirectly, via modification of food web interactions (Duarte et al, ; Kamya et al, ; Queirós et al, ). Previous studies have shown that elevated CO 2 can result in reduced growth rate, disruption of extracellular acid–base balance, alteration of metabolism, lethargy and modification of individual level trade‐offs in energy consuming processes of invertebrates, across different taxonomic groups (Kroeker, Kordas, Crim, & Singh, ; Portner & Farrell, ; Widdicombe & Spicer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated CO 2 may cause some indirect physiological effects with behavioral consequences for predator-prey interactions. High CO 2 levels can indirectly decrease foraging success of brown crab predators (Cancer pagurus) through increased resting metabolic rates and thus less energy allocated to foraging behavior (Wang et al, 2018). Thick shell mussels (Mytilus coruscus) also experience reduced excretion rates in elevated CO 2 conditions, which may indirectly affect chemical cues used by predators although this has not been tested (Wang et al, 2015).…”
Section: Direct Vs Indirect Sensory Effectsmentioning
confidence: 99%